Implications of Sea Based Deterrence for Pakistan - Mr. Majid Mahmood (CISS Insight Journal, 2017)
The nuclear forces of India and Pakistan are evolving and modernizing as the nuclear era nears two decades after their overt nuclearization in 1998. As the diversity and sophistication of nuclear forces increases in the two countries, both South Asian nuclear powers aim to introduce nuclear weapons at sea. India inducted its first nuclear powered ballistic missile submarine INS Arihant in October of 20161 under its ATV project, while Pakistan has successfully test-fired its first ever nuclear-capable submarine-launched cruise missile Babur-III recently2. This demonstration has confirmed earlier speculations by experts that Pakistan is set to field advanced conventional submarine for a nuclear role. As regional nuclear powers move toward triads, however, it is worth examining whether sea-based nuclear weapons are indeed as stabilizing to adversarial dyads as is traditionally held. Cold War analyses of ballistic missile submarine dynamics addressed two large submarine forces, operating in maritime and geostrategic environments that differed from that of South Asia. For the United States, questions of bureaucratic and organizational change, the sustainability of acquisitions, and the advances in antisubmarine warfare capabilities also loomed large in its efforts to establish and maintain a credible assured second-strike delivery system.